STRATEGI LAYANAN BIMBINGAN DAN KONSELING BERBASIS CYBER COUNSELING - Aina Alfira; Syaifullah Nur (JBKPI: Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
Abstact: The research approach used in this study is a qualitative descriptive approach. Qualitative research is research that intends to understand the phenomenon of what is experienced by research subjects, for example behavior, perceptions, motivations, actions and others. The approach or strategy of this research uses a phenomenological approach and data collection methods in this study, namely observation, interviews and documentation. The use of cybercounseling can benefit counselors and counselees from a time and financial standpoint, because the counseling process is not limited by space and time, whenever and wherever the counseling process can be carried out. In addition to the advantages of cybercounseling, it also has weaknesses which until now are still the starting point for criticism from various groups, for example implementation procedures. Besides that, the weakness of cybercounseling is that the counselor does not have enough attention to pay attention to facial expressions, counselee's body language and verbal cues, lack of dynamics, and cannot be clearly controlled behaviors that weaken the dynamics of counseling.Keywords: Service, BK and Cybercounseling